Escalation of Threats and the Impact of Disaster Terrorism on the Security of the Indonesian Presidential: Eskalasi Ancaman dan Dampak Terorisme Bencana terhadap Keamanan Presiden Indonesia - Qusyairi; Karuniasa, Mahawan; Syauqillah, Muhamad (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
Terrorism constitutes a complex, man-made social disaster that threatens national stability, particularly the president as a symbol of state sovereignty. This study analyzes the growing terrorist threats targeting the President of the Republic of Indonesia and examines their multidimensional impacts. The research employs a qualitative approach through literature review, semi-structured interviews, and field observations, with thematic analysis grounded in terrorism studies and security theory. The findings indicate that threats to the president have become increasingly diverse and technologically sophisticated. In addition to conventional physical attacks, emerging threats include cyberattacks, digital disinformation, the use of drones, deepfake operations, lone-actor extremism, and the potential deployment of chemical, biological, radiological, and nuclear (CBRN) materials. Although terrorism incidents in Indonesia have generally declined, risks persist through unconventional attack patterns. Threats against the head of state generate wide-ranging consequences for political stability, social cohesion, economic resilience, and international relations. Therefore, ensuring presidential security requires an integrated, intelligence-based strategy emphasizing early detection, rapid response, and adaptive, sustained interagency coordination.